2021
DOI: 10.3389/pore.2021.1610032
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Activins and Follistatin in Colorectal Cancer According to Clinical Stage, Tumour Sidedness and Smad4 Status

Abstract: This study explored the roles of activins and follistatin in colorectal cancers. Paired malignant and normal colonic tissues were collected from archived paraffin-embedded (n = 90 patients) alongside fresh (n = 40 patients) specimen cohorts. Activin β-subunits, follistatin and Smad4 mRNAs and proteins were measured by real-time PCR and immunohistochemistry (IHC). Mature activin-A, -B, -AB and follistatin proteins were measured by ELISA. Cancer tissues having ≤ the 20th percentile of the Smad4 IHC score were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The sections were studied on a Leica DMi8 microscope and images were acquired from 10 random fields/section with a 20× objective. The IHC Image Analysis Toolbox in ImageJ software (https://imagej.nih.gov/ij/) was used to measure the protein expression, as described elsewhere (38,39).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The sections were studied on a Leica DMi8 microscope and images were acquired from 10 random fields/section with a 20× objective. The IHC Image Analysis Toolbox in ImageJ software (https://imagej.nih.gov/ij/) was used to measure the protein expression, as described elsewhere (38,39).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Many authors have reported that the levels of SMAD4 expression play important roles in many kinds of cancers. [22–24] The roles of SMAD4 in animal models, where SMAD4 is involved in tumor formation and the development of metastasis in prostate, colorectal and pancreatic cancers, have been confirmed. [25] In lung cancer, SMAD4 activates TGF-β signaling and contributes to tumor metastasis by regulating the TGF-β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis with the histopathological staging were based on institutional clinical management guidelines that followed the 8 th edition of the American Joint Committee on Cancer tumor-node-metastasis (TNM) staging system. By retrieving the pathology and surgical reports, tumors located from the cecum to the margin of hepatic flexure were categorized as right-sided cancer (RSC), whilst neoplasms located from the splenic flexure to the rectum were considered left-sided cancer (LSC) ( 4 ). All the retrieved tissue blocks were examined by consultant histopathologists in KAMC to ensure adequacy.…”
Section: Methodsmentioning
confidence: 99%
“…The ImageJ software ( https://imagej.nih.gov/ij/ ) was used to measure the protein expression by the IHC Image Analysis Toolbox, as reported elsewhere ( 4 , 41 ). Briefly, the stained areas (ROI) were identified, and the stain intensity with the percentage of stained areas were measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation